The Whores' Asylum - Katy Darby (United Kingdom Penguin Books Ltd, 2012)
'When you read these words, and all those that follow, I am afraid it must be because I am no longer here to speak them to you. Love is a disease; no doubt of it, and one which has proved mortal to many men down the ages ...' Oxford, 1887: Even as Victoria celebrates the fiftieth year of her reign, a stone's throw from the calm cloisters and college spires lies Jericho, a maze of seedy streets and ill-lit taverns, haunted by drunkards, thieves and the lowest sort of brazen female as ever lifted her petticoats. When Stephen Chapman, a brilliant young medical student, is persuaded to volunteer at a shelter devoted to reforming the fallen women of Oxford, his closest friend Edward feels a strange sense of dread. But even Edward - who already knows the devastating effect of falling in love with the wrong woman - cannot foresee the macabre and violent events that will unfold around them, or stop Diana, the woman who seems destined to drive them apart.
Modern & contemporary fiction (post c 1945)
General (US: Trade)
Keywords: Modern & contemporary fiction (post c 1945); Oxford (England); Great Britain - History - Victoria, 1837-1901